Destination image built by the cinema: The case of "Basilicata Coast to Coast" - Angelo Bencivenga; Livio Chiarullo; Delio Colangelo; Annalisa Percoco (Fondazione Eni Enrico Mattei (FEEM), 2012)
Film tourism, meaning the phenomenon that is born of the desire to visit film locations, has been the object of increasing attention in recent years. This document presents the results of a field research conducted with the aim of analysing the effects of the film Basilicata Coast to Coast, by Rocco Papaleo, on tourism in Basilicata, (a small region in the South of Italy) after its success at the box office and several Italian awards. The film, planned with the involvement of local institutions and stakeholders, pursues the objective of promoting an area that is still largely unknown to national and international tourists. The romantic and naturalistic dimension expressed by Papaleo's film seems to have stimulated the curiosity of tourists and promoted a dreamy but truthful image of the region.
Keywords: Q2; Q26; L82; L83; 330; Film Tourism; Basilicata Coast to Coast; Destination Image; Cinema; Responsible Tourism; Local Tourism Development; Tourismusmarketing; Film; Basilicata